Ethnopedagogy as a Tool for Developing Intercultural Skills in English Language Learning - Arimbawa, Putu Gede (Jurnal Penelitian Mahasiswa Indonesia, 2024)
Globalization demands an educational approach that is responsive to cultural differences, especially in English language learning. Ethnopedagogy, which integrates local culture into the curriculum, offers an effective way to develop students' intercultural skills. This article aims to examine the application of ethnopedagogy in English language teaching and its influence on students' intercultural skills. The method used is Systematic Literature Review (SLR), which analyzes relevant literature on ethnopedagogy and intercultural skills. The results show that the application of ethnopedagogy not only improves English language skills, but also strengthens students' understanding of cultural diversity, as well as communication skills and cross-cultural adaptation. Local culture-based learning has proven to be effective in motivating students and creating an inclusive learning environment. In conclusion, ethnopedagogy is an effective approach to preparing students for global challenges, with suggestions that educators integrate this approach into the English curriculum.